PERLINDUNGAN KONSUMEN BAGI KORBAN KERACUNAN MAKANAN JAJANAN LATIAO DI SDN CIDADAP I KECAMATAN SUKARAJA: Consumer Protection for Victims of Food Poisoning from Latiao Snacks at SDN Cidadap I Sukaraja District - Gheryl Sebastian Sijabat; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2025)
Latiao is a processed food product imported from a manufacturer in China. However, an extraordinary food poisoning incident occurred at SDN Cidadap I in Sukaraja District as a result of consuming this product. The issue addressed in this study revolves around consumer protection for Latiao product consumers and the legal actions that can be taken. This research uses a normative and descriptive approach, employing secondary data to support primary data, which is then analyzed qualitatively and concluded deductively. The study findings conclude that the business operator violated Article 4, letter (a) of the Consumer Protection Law (UUPK) by failing to ensure that the product met consumers' safety, health, and security standards. Other violations identified include Article 7, letter (b) regarding the provision of accurate information about the product, Article 7, letter (d) on product quality, Article 8, letter (a) on compliance with legal product standards, as well as letters (d) and (e) concerning the product's condition and processing. Other regulations disobeyed are Article 86 of the Food Law on product distribution and Article 90 regarding harmful content. It also reveals that the victims have not taken any legal action following the poisoning incident.